Civil society participation in city governance - Kozak, Alicja (Udział społeczności w sprawowaniu rządów nad miastem, 2021)
The author states that society itself is the most important stakeholder in a city. The reasons for such state were examined along with the implications what this means for both inhabitants and authorities. In the section that follows, the conscious city-changing actions of inhabitants were taken into consideration, with the emphasis on urban activism. The last part again concerns inhabitants’ actions in a converse, passive way, which is perceived as a form of active but unconscious participation in governance in this research.
Biblioteka Regionalisty, 2021, Nr 21, s. 52-61
Keywords: society; participation; governance; city; społeczeństwo; partycypacja; rząd; miasto